First record of the genus Microstenus Szépligeti (Hymenoptera: Ichneumonidae: Cryptinae) from China, with description of one new species and a key to world species - Li, Tao; Sun, Shu-Ping; Sheng, Mao-Ling (Zootaxa, 2020)
The genus Microstenus Szépligeti, 1916 (Hymenoptera: Ichneumonidae: Cryptinae) is newly recorded from China based on a new species, Microstenus rufithorax Sheng, Li & Sun, sp. nov., collected from Guangxi Zhuang Autonomous Region, Oriental part of China. Illustrations of the new species are provided. A key to the world species of this genus is also provided.